Tindak Kejahatan Genosida Etnis Rohingya Di Myanmar Dari Prespektif Hukum Pidana Internasional (Jurnal Begawan Hukum (JBH), 2025)
The crime of genocide is related to ethnic or cultural extermination and also includes crimes against political groups because these groups are difficult to identify which will cause international problems in a country. The crime of genocide in international criminal law is an extraordinary crime and has become a prohibited act which was later stated in the 1948 Genocide Convention, the statute of the International Criminal Tribunals for the Former Yugoslavia (ICTY), the statute of the International Criminal Tribunals for Rwanda (ICTR) and the 1998 Rome statute. This study aims to determine the crime of genocide experienced when viewed in International Law and how to resolve disputes over crimes of genocide under international law.This research uses doctrinal or juridical normative research. Sources of legal information use primary legal materials (regulations and related documents) for further qualitative analysis. The approach used is a conceptual approach, a statutory approach, and a case law approach in helping to solve the problem formulation. The results of the study stated that the main cause of the crime of genocide was motivated by the struggle for the rights of ethnic minorities and the existence of fanatical and racial religions that were shown in cultural discrimination. The crimes committed by the Myanmar government by the Rohingya Muslims constitute an international crime of genocide, because it has fulfilled several main elements, namely mass murder, discrimination against religious minorities, is carried out systematically, and aims to eliminate certain ethnic groups and groups.